Conditions of aircraft cockpit protection against moisture condensation - Хлистун, О.І. (Proceedings of National Aviation University (archive), 2004)
Presented is the methodic of rated conditions determination for the design parameters choice of aircraft hermetic cabin glazing heat protection against water condensation.